Perancangan Aplikasi Crowdfunding Berbasis Website - Nararia Ningrat, Putu Vidi; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
In this modern era many technology have been created to help human do their work. One of them is Crowdfunding, where is this app or website that can funding easily. Crowdfunding make it easy for businessman that really need funds for theire business while development. User can also giving funds to various project that being development by businessman. This Crowdfunding sites create by JavaScript Framework with Database from GraphQl.